Perlindungan Dan Penyelesaian Sengketa Kosumen Sektor Jasa Keuangan - Hasanal Mulkan; Veni Ardea Regita; Marissa Ikhsan; Fathya Faradilla; Muhammad Rizky Kurniawan (JUSTICIA SAINS - Jurnal Ilmu Hukum, 2023)
Disputes in the financial services sector can occur if there is a difference in understanding between the institution and the consumer regarding a service product from the related financial institution or from the institution's negligence in fulfilling its obligations. Consumer protection is all efforts to provide legal certainty to consumers. The PK Law is the legal basis for legal protection for consumers, while the OJK Law is the Constitution of the establishment of Financial Institutions, in this case the OJK as an independent body that regulates, supervises, inspects and investigates in the financial services sector as well as aims to protect consumers as users of financial services. In the applicable regulations, consumer protection is manifested in the obligations of financial services business actors related to complaint facilitation, complaint settlement facilities, internal control, consumer protection supervision, and sanctions. Settlement of disputes in the financial services sector first through the Financial Services Institution, if no settlement is reached, then proceed with settlement in court or out of court.